Infection of neonates with Staphylococcus aureus and methicillin-resistant Staphylococcus aureus at Dormaa Presbyterian Hospital, Ghana - Jerome Adinkrah Obeng; William Gariba Akanwariwiak; Eugene Adade; Augustina Angelina Sylverken (Microbiology Spectrum)
ABSTRACT Staphylococcus aureus is the second most common pathogen found in all cases of nosocomial infections globally. Methicillin-resistant Staphylococcus aureus (MRSA) is a common cause of infection among preterm and critically ill newborns in neonatal intensive care units. Newborns are predominantly susceptible to S. aureus and MRSA colonization and infection due to their weaker immune systems. Treating infections in newborns associated with S. aureus and MRSA has proven challenging due to decreasing susceptibility to first-line antibiotics, leaving clinicians with few treatment options. This cross-sectional study aimed to determine the prevalence of hospital-acquired MRSA among neonates at the Dormaa Presbyterian Hospital in Ghana, the susceptibility profile to selected antibiotics, and the associated risk factors. Venous blood samples were taken from each of the neonatal participants and inoculated into Brain Heart Infusion broth. Standard biochemical tests were performed, and 36.0% (9/25) of the S. aureus isolates were identified as MRSA. The MRSA isolates were more susceptible to ciprofloxacin, levofloxacin, gentamicin, co-trimoxazole, tetracycline, and cephalexin but resistant to cloxacillin, ampicillin, roxithromycin, and lincomycin. The study found that gestational period (χ2 = 3.865, P = 0.049) and longer length of hospital stay (χ2 = 10.911, P = 0.012) were statistically significant for S. aureus and MRSA infection. Surveillance systems should be put in place by health authorities at the hospital, targeting decolonization of MRSA strains at the hospital as well as monitoring antibiotic resistance that occurs through inappropriate access and use of antibiotics.IMPORTANCEThe methicillin-resistant Staphylococcus aureus (MRSA) threat has become a source of concern for medical facilities and patients worldwide. MRSA infections are more difficult to treat, resulting in higher rates of morbidity and mortality. Prematurity, low birth weight, method of delivery, mode of resuscitation after birth, feeding method, prolonged hospital stay, kangaroo mother care, and overcrowding in hospitals are all risk factors for MRSA infection. Overcrowding is a common issue in the Dormaa Presbyterian Hospital (DPH), as it is in most hospitals around the country. The study intended to bring to the notice of mothers, hospital staff, and caregivers the risk factors associated with Staphylococcus aureus and methicillin-resistant Staphylococcus aureus among neonates at DPH.